Food allergy safety: a descriptive report of changing policy in a single large medical center - Rivki Harari; Orly Toren; Yuval Tal; Tair Ben-Porat (BMC, 2021)
Abstract Background Food allergy can result in life-threatening anaphylaxis and is considered an increasing public health burden. Hospitalized patients are dependent on the hospital menu to meet their nutritional needs; thus, errors in the meals provided can have a substantial impact on patients' health outcomes. In Israel, no specific policy protocol exists to ensure food allergy safety in the setting of a hospital foodservice system. Objectives This paper has two aims: 1) to provide an in-depth review of food allergy as a major public health concern and 2) to report actions taken in a single large medical center, as an ongoing project that aimed to ensure patients' safety, and which ended in developing policy on this matter. Results During the years 2017-2019, we initiated several interventions with the goal of achieving food allergy safety and ensuring quality of care for patients with food allergies at Hadassah Hebrew University Medical Center. These included integrating food management safety into the computerized foodservice system, highlighting labels on patients' food trays, introducing safety checks into the process of food delivery to hospitalized patients; and ensuring the nutritional requirements of patients with allergy restrictions. Moreover, changes were made in specialized menus for patients with various types of food allergy, and specific procedures were implemented regarding enteral feeding, to prevent accidental allergen exposure. All the procedures were incorporated into a written protocol that applies to all hospital employees, and the staff received the relevant training. Conclusions Our experience suggests that methods for food allergy safety should be promoted, and that an established policy and suitable set of guidelines on this matter is required. This clearly mandates collaboration between the various sectors of the hospital, including management and the computer department; and the medical, nursing, dietetics and kitchen staffs. Furthermore, routine ongoing knowledge training programs for medical teams and kitchen staff are crucial for such implementational changes. In a technological world, computerized systems delivering food to hospitalized patients must be adapted such as to create a uniformly safe food environment of healthcare systems, and developing a suitable policy should be prioritized accordingly by hospitals across Israel, with collaboration and synergy between institutions management and the departments of nutrition and patient safety and risk management.